REORGANIZACIÓN CONTABLE EN LA EMPRESA COMERCIAL “TAPICENTRO” DE LA CIUDAD DE LOJA, PERIODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE 2017 - Bazarán Guamán, Verónica del Pilar (2019)
COMMERCIAL COMPANY "TAPICENTRO" OF THE CITY OF LOJA, PERIOD FROM 01 SEPTEMBER TO DECEMBER 31, 2017", has the purpose of improving the current accounting management of the company and is based on the objectives traced in the investigation, the same ones that have relation with the reorganization of the accounting system, that will be of great help so that the owner obtains more effective results of the economic activity that realizes and therefore takes correct decisions. This thesis work was initiated in compliance with the objectives set for which was made the physical verification in its entirety of the assets, values and obligations of the company to structure the initial inventory. Then proceeds with the preparation of the chart of accounts determining the respective coding for each of them, and based on this the respective manual was developed describing the appropriate use of the same in order to facilitate its registration in the accounting entries; which was done taking into account the needs of the company. Then the registers and assistants were elaborated for the control and accounting of the economic-financial operations that are generated in the Commercial Company "TAPICENTRO", and thus be able to apply the accounting process; where it proceeds to order, analyze and interpret all the information and supporting documents received that support the movements that the company has had, allowing the acquisition and sales assistants to be used as base information for the preparation of the 5 transaction memorandum, which made it possible to register accounting in the Daily Book and therefore in the General Ledger, Verification Balance and worksheet to achieve structuring the Financial Statements. In order to develop this whole process, the methodology proposed and used was taken into account, since it allowed a complete compilation of the essential information to carry out the accounting reorganization in the business. In conclusion, this thesis work is a significant contribution to the Commercial Enterprise "Tapicentro", because it allowed the owner to corroborate the economic reality of the same and according to its results facilitated decision making with the sole objective of improving its economy .